2006
DOI: 10.1093/jac/dkl360
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical hypothyroidism in HIV-infected subjects

Abstract: The occurrence of subclinical hypothyroidism in HIV-positive patients seems to be related to the increase in total cholesterol serum levels occurring after HAART initiation. Thyroid function should be monitored in all HIV-infected subjects, especially in those starting HAART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 13 publications
3
35
0
7
Order By: Relevance
“…This study also found a similarly high prevalence of 8.3% for low fT3 and fT4 in the presence of a normal TSH value and 12.5% each for isolated low fT3 and fT4 respectively among the control-HIV group (i.e. HIV infected people who were not on HAART, [ Table-3] a finding which is in agreement with that by Bongiovani et al, [22] and Quirino et al [23]. In their study in Italy in 2006, Bongiovani and his group studied a total of 190 HIV infected subjects who they classified three groups, G1, G2 and G3.…”
Section: Discussionsupporting
confidence: 91%
“…This study also found a similarly high prevalence of 8.3% for low fT3 and fT4 in the presence of a normal TSH value and 12.5% each for isolated low fT3 and fT4 respectively among the control-HIV group (i.e. HIV infected people who were not on HAART, [ Table-3] a finding which is in agreement with that by Bongiovani et al, [22] and Quirino et al [23]. In their study in Italy in 2006, Bongiovani and his group studied a total of 190 HIV infected subjects who they classified three groups, G1, G2 and G3.…”
Section: Discussionsupporting
confidence: 91%
“…A variety of endocrine disorders including thyroid dysfunction has been described in HIV infected patients, and recent studies have reported subclinical hypothyroidism as the most common thyroid abnormality in this population [1][2][3][4][5][6][7][8][9][10][11]. Treatment of HIV infected patients with highly active antiretroviral drugs (HAART), especially with stavudine [1,8,9,11], increase in total cholesterol serum levels after HAART initiation [2], and history of opportunistic infections [3] is among contributors of subclinical hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of HIV infected patients with highly active antiretroviral drugs (HAART), especially with stavudine [1,8,9,11], increase in total cholesterol serum levels after HAART initiation [2], and history of opportunistic infections [3] is among contributors of subclinical hypothyroidism. Drugs like rifampin, Kaposi's sarcoma, and mycobacterial infections may additionally impair thyroid function [10,[12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…La indicación de exámenes de tamizaje en sujetos asintomáticos es controvertida, pero ha sido recomendada por algunos autores 7,9,15,17,20,21 , debido al beneficio clínico potencial del tratamiento en pacientes con disminución de la función tiroidea y, también, debido a que podría servir como marcador indirecto de la progresión de la infección por VIH 15,16,19,39 . En suma, aun cuando no se logró demostrar una mayor prevalencia de hipotiroidismo en este grupo de pacientes respecto a la población general, consideramos recomendable monitorizar la función tiroidea en estos sujetos, ya que las manifestaciones clínicas de la disfunción tiroidea no son específicas y estas alteraciones podrían deteriorar la calidad de vida y el pronóstico de los pacientes infectados por el VIH a largo plazo.…”
Section: Discussionunclassified
“…El hipertiroidismo tiene una prevalencia < 1% 13 .En etapas precoces de la infección por VIH se ha encontrado aumento de la proteína transportadora de hormonas tiroideas, con títulos de anticuerpos antitiroideos normales, excepto por casos aislados de anticuerpos antitiroglobulina elevados 6,10,11,17 . La etiopatogenia de las alteraciones endocrinas es multifactorial, en pacientes no tratados predomina el efecto directo del virus, el compromiso de la glándula por infecciones oportunistas o infiltración tumoral y el impacto de la inflamación sistémica 18,19 ; con el uso de la terapia antirretroviral (TARV) se agregan los efectos secundarios de ésta, que influyen en la disfunción tiroidea [19][20][21] . Entre los factores asociados al desarrollo de hipotiroidismo se han identificado: presencia de infecciones oportunistas 9 , recuento bajo de linfocitos CD4 22,23 y TARV, específicamente el uso de estavudina 7,8,20,24 .…”
unclassified